LINGUISTIC AND CULTURAL CHARACTERISTICS OF ENGLISH AND UZBEK PROVERBS - Boboniyozova Iroda Qurboniyozovna (Western European Studies, 2024)
The interpretation and expression of phraseological units, i.e. proverbs and proverbs, in English and Uzbek languages, the problems that arise in the process of translating proverbs from one language to another or finding an alternative equivalent were analyzed in this article through examples. Also, the linguistic and cultural connection and differences of English and Uzbek folk proverbs of two non-fraternal nations were studied
Keywords: Proverb; language; phraseology